The effect of initial stresses on harmonic stress fields within the stratified half plane - Akbarov, SD; Ozaydin, O (GAUTHIER-VILLARS/EDITIONS ELSEVIER, 2001)
The effect of initial stresses on dynamic (harmonic) stress fields within an elastic stratified half plane is investigated. It is assumed that the point-located harmonic force acting on the free plane of the layer by which the half plane is stratified causes this stress field. By employing displacement potentials and the exponential Fourier transform the governing system of partial differential equations of motion is solved. The necessary inverse transformations including rigorous mathematical complexity is performed numerically. The analysis of the numerical results, which shows the influence of the homogeneous initial stresses on the distribution of the stresses on the inter-medium plane, is made. These analyses are examined for various problem parameters and it is assumed that the material of both the layer and the half plane is homogeneous, isotropic, compressible and linearly elastic. It has been observed that the initial stresses may change significantly the values of the superimposed harmonic stresses. (C) 2001 Editions scientifiques et medicales Elsevier SAS.
Keywords: harmonic force; initial stress; stratified half plane; stress distribution; INCOMPRESSIBLE ELASTIC PLATE; DISPERSION-RELATION; WAVES; DEFORMATIONS; MEDIA; Mechanics